PENGARUH KERAGAMAN GENDER DEWAN KOMISARIS DAN CORPORATE GOVERNANCE TERHADAP PRAKTIK MANAJEMEN LABA - Pasaribu, Maxielant Joshua Firdaus; Kawedar, Warsito (Diponegoro Journal of Accounting, 2024)
This study examines the effect of Board of commissioners gender diversity and corporate governance on earnings management practices through the presence of female commissioners, female independent commissioners, the number of women on the board of commissioners, board size, and independent commissioners on earnings management in well-known public companies in Indonesia. This study uses companies listed on the Indonesia Stock Exchange (IDX) that provide regular and complete financial reports and annual reports from the LQ45 index in 2017-2021, and provide data by the research variables. Hypothesis testing was carried out using multiple linear regression to test the effect of each independent variable on the dependent variable. The results showed that gender diversity through the number of women on the board of commissioners has a significant negative effect on earnings management. Meanwhile, the presence of female commissioners, female independent commissioners, the board size, and independent commissioners on earnings management is not significant.